Live liver donation, ethics and practitioners: 'I am between the two and if I do not feel comfortable about this situation, I cannot proceed'. Issue 3 (26th March 2013) - Thomas, Elin H; Bramhall, Simon R; Herington, Jonathan; Draper, Heather
Abstract : This paper discusses the views of 17 healthcare practitioners involved with transplantation on the ethics of live liver donations (LLDs). Donations between emotionally related donor and recipients (especially from parents to their children) increased the acceptability of an LLD compared with those between strangers. Most healthcare professionals (HCPs) disapproved of altruistic stranger donations, considering them to entail an unacceptable degree of risk taking. Participants tended to emphasise the need to balance the harms of proceeding against those of not proceeding, rather than calculating the harm-to-benefits ratio of donor versus recipient. Participants' views suggested that a complex process of negotiation is required, which respects the autonomy of donor, recipient and HCP. Although they considered that, of the three, donor autonomy is of primary importance, they also placed considerable weight on their own autonomy. Our participants suggest that their opinions about acceptable risk taking were more objective than those of the recipient or donor and were therefore given greater weight. However, it was clear that more subjective values were also influential. Processes used in live kidney donation (LKD) were thought to be a good model for LLD, but our participants stressed that there is a danger that patients may underestimate the risks involved in LLD if it is too closely associated with LKD.